An Alpha-1A Adrenergic Receptor Agonist Prevents Acute Doxorubicin Cardiomyopathy in Male Mice. - Megan D Montgomery; Trevor Chan; Philip M Swigart; Bat-Erdene Myagmar; Rajesh Dash; Paul C Simpson (PLoS ONE, 2017)
Alpha-1 adrenergic receptors mediate adaptive effects in the heart and cardiac myocytes, and a myocyte survival pathway involving the alpha-1A receptor subtype and ERK activation exists in vitro. However, data in vivo are limited. Here we tested A61603 (N-[5-(4,5-dihydro-1H-imidazol-2-yl)-2-hydroxy-5,6,7,8-tetrahydronaphthalen-1-yl]methanesulfonamide), a selective imidazoline agonist for the alpha-1A. A61603 was the most potent alpha-1-agonist in activating ERK in neonatal rat ventricular myocytes. A61603 activated ERK in adult mouse ventricular myocytes and protected the cells from death caused by the anthracycline doxorubicin. A low dose of A61603 (10 ng/kg/d) activated ERK in the mouse heart in vivo, but did not change blood pressure. In male mice, concurrent subcutaneous A61603 infusion at 10 ng/kg/d for 7 days after a single intraperitoneal dose of doxorubicin (25 mg/kg) increased survival, improved cardiac function, heart rate, and cardiac output by echocardiography, and reduced cardiac cell necrosis and apoptosis and myocardial fibrosis. All protective effects were lost in alpha-1A-knockout mice. In female mice, doxorubicin at doses higher than in males (35-40 mg/kg) caused less cardiac toxicity than in males. We conclude that the alpha-1A-selective agonist A61603, via the alpha-1A adrenergic receptor, prevents doxorubicin cardiomyopathy in male mice, supporting the theory that alpha-1A adrenergic receptor agonists have potential as novel heart failure therapies.